PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INTODUKTION DENGAN APLIKASI ZOOM DALAM MENINGKATKAN HASIL BELAJAR MATA KULIAH ANALISIS RIIL II PRODI PENDIDIKAN MATEMATIKA (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
This study aims to determine whether there is any influence and student response to the application of the problem-based instruction learning model with the zoom application in improving learning outcomes in Real Analysis II subjects. This type of research is classroom action research. The subjects of action research are students of semester 1 of Mathematics Education at PGRI Mahadewa University of Indonesia for the academic year 2020/2021, and the object of this research is the study of understanding the material of Sequences and Line Limits in Real Analysis II courses and student responses to Problem-based instruction learning models. In this study, two cycles were used and each cycle went through four stages of the activity process which included: planning, acting, observing, evaluating and reflecting. To obtain complete data, this study uses test and observation methods. The results of action research are: (1) There is an effect of the application of the Problem-based instruction learning model with the zoom application in improving learning outcomes (2) There is a student response to the application of the Problem-based instruction learning model with the zoom application in improving the learning outcomes of the Real Analysis II subject for students semester VII B Mathematics Education Study Program 2020/2021 is good.